Effects of self-reported sensitivity and road-traffic noise levels on the immune system - Kim, Ahra; Sung, Joo Hyun; Bang, Jin-Hee; Cho, Seung Woo; Lee, Jiho; Sim, Chang Sun (PloS one, 2017)
Sensitivity to noise, particularly road traffic noise, can increase cortisol levels and result in changes in immune system biomarkers. Therefore, continuous exposure to noise can have an effect on immune function, hormonal levels, and cardiovascular function, leading to hypertension and stress. The purpose of this study was to investigate the changes in stress-and immune system-related biomarkers according to the self-reported sensitivity to noise and exposure to road traffic noise, to ultimately determine the potential effects of noise on health. A survey was conducted through questionnaire (ISO/TS 15666) sent to 172 female subjects in Korea, including 128 from Ulsan and 44 from Seoul. The average noise level was calculated, and blood samples were collected for measurements of cortisol levels, Natural killer (NK) / Natural killer T (NKT) cell populations, and NK cell activity (through measurements of interleukin-12 (IL-12) and interferon-gamma (INF-γ) concentrations). Multivariate linear regression analysis of the measured biomarkers according to the road traffic noise level and self-reported noise sensitivity was conducted adjusting for the effects of age, alcohol status, smoking status, regular exercise, and residence period. IL-12 levels increased, whereas the NKT cell population decreased with increasing noise levels. The results further suggested that cortisol levels are more influenced by the subject's sensitivity to noise than to the level of chronic road traffic noise. Therefore, noise appears to have the largest effect on IL-12 levels as well as the population and activity of NKT cells. In conclusion, our results suggest that low-level road traffic noise and sensitivity to noise can affect health by causing changes in the immune response through mechanisms other than increased cortisol.